THE CORRELATION BETWEEN VOCABULARY MASTERY AND READING COMPREHENSION OF THE EIGHTH-GRADE STUDENTS OF SMPN 1 BLAHBATUH IN ACADEMIC YEAR 2021/2022 - Pande Kadek Dewintha Tiara; Anak Agung Istri Yudhi Pramawati; I Gusti Agung Putri Wirastuti (Academic Journal on English Studies (AJOES), 2022)
The present study is an ex-post facto research with correlation design was intended to figure out the significant correlation between vocabulary mastery and reading comprehension of the eighth-grade students of SMPN 1 Blahbatuh in academic year 2021/2022. The samples of the research consisted of 60 students which were chosen by means of random sampling method with lottery system. The data were collected through administering the research instruments which were in the form of structured matching cloze procedure test and short answer test. The obtained data were statistically analyzed by using Pearson product moment correlation and t-test. The results of the data analysis clearly revealed the alternative hypothesis was accepted. In other words, the research findings confirmed that there is significant correlation between vocabulary mastery and reading comprehension of the eighth-grade students of SMPN 1 Blahbatuh in academic year 2021/2022.